Pengembangan Instrumen Asesmen Berbasis Higher Order Thinking Skills pada Materi Komponen Ekosistem dan Interaksinya di SMA Negeri 1 Tondano - Imelda Febrianti Makalalag; Arrijani Arrijani; Anatje Lihiang (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
The rapid demands of 21st-century education require assessment instruments capable of measuring higher order thinking skills (HOTS), while classroom assessments in many schools are still dominated by lower order thinking skills (LOTS). This study aims to develop a HOTS-based assessment instrument on ecosystem components and their interactions at SMA Negeri 1 Tondano and evaluate its feasibility based on validity, reliability, item difficulty, discriminating power, and student responses. The study used a Research and Development (R&D) approach with the 3-D model consisting of define, design, and develop stages. The subjects involved 32 tenth-grade students and one biology teacher. The instrument consisted of 20 multiple-choice questions and 5 essay questions designed to measure cognitive levels of analysis (C4), evaluation (C5), and creation (C6). Data were collected through expert validation, validity and reliability testing, item analysis, and student response questionnaires. The results showed an expert validation score of 97.2 (very valid), a trial score of 77.25 (good), and a student response score of 89.87 (very valid). Item analysis indicated that most items were valid, reliable, and had balanced difficulty levels. The developed HOTS-based assessment instrument is valid, practical, and effective for biology learning evaluation.